Unjuk Kinerja Sistem Aerasi Dalam Kotak Penyimpanan Kentang (Solanum tuberrosum L) Tipe Kotak - Setiyo, Yohanes; Siata, Dandy Zulfikar Sulthan; Arthawan, I Gusti Ketut Arya (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 1 (2022), 2022)
The purpose of this study was to determine the performance of the box type potato storage aeration system in terms of changes in temperature and RH of the air during storage. Research on a box type aeration system for potato storage was carried out by measuring the temperature and RH of the incoming air, the temperature and the RH of the outgoing air during storage of potatoes for 21 days. In addition, calculating the heat of respiration, heat to increase the temperature of potatoes, heat to evaporate water and heat lost to the environment using a simple mathematical model approach. The results showed that the temperature and RH of the room and the incoming air flow tended to form a linear pattern, while the RH of the process room and the outgoing air flow tended to form a polynomial pattern. The temperature of the potato storage room was in the range of 24.07-25.70oC and the RH was in the range of 56.0-65.6%. The heat value of respiration varied between 261.42 - 311.88 k.Joule/kg potato tubers, because the storage temperature was 24.07-25.70oC. The heat generated by the respiration process used to evaporate water from the potato tubers to the environment is 6.01±0.3% on average, the average heat to raise the temperature of the potato tubers and the air temperature around the potato is 24.08±1, 3%, and the average heat loss to the environment with the flowing air is 59.89±3.4%.